Interaction of transient fast flows with biological cells in microfluidic confinement - Li, Fenfang (2015)
This thesis deals with the interaction of biological cells with transient fast flows mainly from bubbles in microfluidic confinement. These interactions can be utilized to stretch and porate cell membranes toward a label-free biomarker for human diseases, and drug or gene delivery, respectively. The rapid expansion and collapse of a single laser-induced cavitation bubble generate a strong shear flow, which is mainly located within the boundary layer close to the bubble. This leads to impulsive stretching of red blood cells with large strains while larger spherical cancer cells have to be stretched by an extension flow with inertial focusing. The deformability of cancer cells is found to correlate with their invasive potential. Besides, the fast jetting flow from shock wave/cavitation bubble-gas bubble interaction is exploited for localized cell membrane poration. We also study this kind of fast jetting flow in detail with different geometrical arrangements of the gas bubbles and some novel phenomena are observed.